Automatic Emergency Lamp - Rizki Pratama Putra; Adimas Aglasia (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2018)
Abstract – The use of lights in daily activities is needed by humans, especially at night. However, when power failure, it will be a problem because the lights will also die. Therefore, in need of an alternative power source other than the PLN to replace the electric source of the lamp when the power off. To overcome this the authors use the battery as a replacement source of electrical voltage from the PLN which at the same time can be refilled automatically when the PLN electric current is on.keywords -- Index terms- Lamp, Emergency, Battery, Power